Subterranean Worlds: A Critical Anthology - Haynes, RD (Nineteenth Century French Studies, 2006)
Peter Fitting, Director of the Cinema Studies Program at the University of Torontoregards this book as "somewhere between a hobby and an obsession," drawing, as itdoes, on his interest in literary utopias and science fiction. In it he traces the theme ofa subterranean world through some fifteen novels, from the anonymous Relation d'unvoyage du Pole Arctique au Pole Antarctique (1721) to Edgar Rice Burroughs's At theEarth's Core (1914). Each chapter offers a brief introduction, including a synopsis of thenarrative, followed by extracts from the novel, chosen to indicate how the adventurer-narratorarrived there, a description of the subterranean world, how it is illuminatedand, where appropriate, the society that exists there.